Implementasi Pendidikan Karakter Melalui Pembiasaan Baik Profil Pelajar Pancasila Peserta Didik Fase B - Fatimah, Nurulul; Sumarno; Ida Dwijayanti (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study aims to analyze the implementation of character education through positive habits in Phase B students to develop the Pancasila Student Profile. The background of this research highlights the importance of character education in the Indonesian education system to cultivate a generation with noble character, responsibility, and national spirit. This research employs a qualitative method with a case study approach conducted in an elementary school in Indonesia. Data were collected through in-depth interviews with teachers, direct observations, and document analysis related to character education programs. The results indicate that the program of positive habits, such as activities of mutual cooperation, discipline, and responsibility, has effectively shaped students' character in alignment with Pancasila values. Teachers play a crucial role as models and facilitators in this process. The conclusion of this study is that the implementation of character education through positive habits can significantly support the achievement of the Pancasila Student Profile, provided it is supported by the active involvement of all related parties, including teachers, parents, and the community.